Magnetic phase coexistence and metastability caused by the first-order magnetic phase transition in the Heusler compound Mn2PtGa - Nayak, A. K.; Sahoo, R.; Mejia, C. Salazar; Nicklas, Michael; Felser, Claudia (Journal of Applied Physics, 2015)
The Heusler compound Mn2PtGa exhibits a first-order ferrimagnetic (FI) to antiferromagnetic (AFM) phase transition, in contrary to the conventional martensitic structural transition displayed by their close relatives, the Heusler shape-memory alloys. With the help of isofield and isothermal magnetization experiments as well as magnetic relaxation measurements, we exemplify the presence of a magnetic-phase coexistence and a metastable magnetic behavior below the FI-AFM phase transition. Field cooling across the FI-AFM transition leads to a nucleation of a supercooled FI phase below the transition temperature, where the fraction of the supercooled phase depends upon the strength of the cooling field.
CRIS-Team Scopus Importer:2023-03-20